Mirtazapine fatal poisoning. (July 2017) - Vignali, Claudia; Groppi, Angelo; Brandolini, Francesca; Avato, Francesco Maria; Talarico, Anna; Gaudio, Rosa Maria; Morini, Luca
Highlights: We describe a fatal case of mirtazapine self-poisoning. We performed the analysis of mirtazapine and N -desmethylmirtazapine by LC–MS/MS. We compare our results with those of previously published cases. Abstract: Mirtazapine is a noradrenergic and specific serotoninergic antidepressant agent that stimulates norepinephrine and serotonin release while also blocking serotonin receptors (5-HT2 and 5-HT3). Although the drug is used extensively, at present we do not know of any fatal cases due to mirtazapine alone. On the contrary, the published literature describes several fatal poisoning cases related to the intake of mirtazapine together with other drugs. Here we describe a fatal case of mirtazapine self-poisoning, since the other drug detected (lorazepam), was within the therapeutic range. Analyses were performed by LC–MS/MS on body fluids and a hair sample and mirtazapine concentration measured in blood was very high: 9.3 mg/L. N -Desmethylmirtazapine was also quantitated. We then compared our results with those of previously published cases. In conclusion, even though mirtazapine can be considered a relatively safe drug, taking a large amount alone or in combination with other drugs, could lead to death.